Estimation of genetic parameters for body weight of Alabio and Mojosari ducks at starter period - Prasetyo, L. Hardi; Susanti, Triana (Indonesian Journal of Animal and Veterinary Sciences, 2007)
A selection program is one of many important tools in livestock breeding in improving the quality of breeding stock. The choice of an effective selection method requires some information on the value of genetic parameters for some economically important traits, such as heritabilities and genetic correlation coefiicients. This experiment used 25 drakes and 100 ducks of each Alabio and Mojosari ducks, mated at random 1 drake to 4 ducks. A number of ducklings were obtained from each mating in each population, and their body weights were observed from hatching to 8 weeks old. Results showed that the heritability estimation for body weight to 8 weeks old were generally low either in Alabio or in Mojosari, ranging between 0.061 to 0.227. The highest heritability estimation was obtained for 6-week body weight 0.151 for Alabio and 0.227 for Mojosari ducks. The estimates of genetic correlation among body weights varied widely but generally high. It is concluded that 6-week body weight can be considered as a selection criterion depending on the selection objective in the local Indonesian ducks. Key Words: Heritability, Genetic Correlation, Ducks